Glycocalyx Impairment in Vascular Disease: Focus on Inflammation - Qu, Jing; Cheng, Yue; Wu, Wenchao; Yuan, Lixing; Liu, Xiaojing (Frontiers in Cell and Developmental Biology, 2021)
The glycocalyx is a complex polysaccharide-protein layer lining the lumen of vascular endothelial cells. Changes in the structure and function of the glycocalyx promote an inflammatory response in blood vessels and play an important role in the pathogenesis of many vascular diseases (e.g., diabetes, atherosclerosis, and sepsis). Vascular endothelial dysfunction is a hallmark of inflammation-related diseases. Endothelial dysfunction can lead to tissue swelling, chronic inflammation, and thrombosis. Therefore, elimination of endothelial inflammation could be a potential target for the treatment of vascular diseases. This review summarizes the key role of the glycocalyx in the inflammatory process and the possible mechanism by which it alleviates this process by interrupting the cycle of endothelial dysfunction and inflammation. Especially, we highlight the roles of different components of the glycocalyx in modulating the inflammatory process, including components that regulate leukocyte rolling, L-selectin binding, inflammasome activation and the signaling interactions between the glycocalyx components and the vascular cells. We discuss how the glycocalyx interferes with the development of inflammation and the importance of preventing glycocalyx impairment. Finally, drawing on current understanding of the role of the glycocalyx in inflammation, we consider a potential strategy for the treatment of vascular diseases.